Vertical Price Transmission in Soybean, Soybean Oil, and Soybean Meal Markets - Simanjuntak, Josua Desmonda; Cramon-Taubadel, Stephan von; Kusnadi, Nunung; Suharno (Jurnal Manajemen dan Agribisnis, 2020)
Soybean is becoming a prominent agricultural industry due to its versatility of use as inputs for different industrial sectors. Soybean products have a high value and are profitable since its huge supply and wide demand. The soybean economic value does belong to the commercial use of its joint products, soybean meal, and soybean oil. Joint product theory assumes the price of soybeans can be represented as a weighted average of returns from soybean meal and soybean oil less than the processing margin. This indicates there are price relationships between soybean as a raw product towards its meal and oil through crush processing. Therefore, the objective of this research is to investigate the price transmission between these three products and analyzed factors that influencing them. Monthly time series data in respect of international prices were obtained. Augmented Dickey-Fuller (ADF) test and the Johansen cointegration technique were utilized to test the stationarity and the long-run relationship between three variables respectively. The result indicates the existence of one cointegrating long-run equilibrium relationship between these variables. The Vector Error Correction Model (VECM) estimates revealed that soybean price is the only one that reacts to correct equilibrium since oil and meal have huge markets.Keywords: soybean, soybean meal, soybean oil, joint product, VECM